Management of trichobezoar: About 6 cases - Besma Haggui; Saida Hidouri; Amine Ksia; Meriem Oumaya; Sana Mosbahi; Marwa Messaoud; Sabrine Ben Youssef; Lassaad Sahnoun; Mongi Mekki; Mohsen Belghith; Abdellatif Nouri (Wolters Kluwer Medknow Publications, 2022)
Background: Trichobezoar is an uncommon clinical entity in which ingested hair mass accumulates within the digestive tract. It is generally observed in children and young females with psychological disorders. It can either be found as an isolated mass in the stomach or may extend into the intestine. Untreated cases may lead to grave complications. Material and Methods: We retrospectively analyzed the clinical data of six patients treated for trichobezoar in Monastir pediatric surgery department during 16-year-period between 2004 and 2019. Imaging (abdominal computed tomography and upper gastroduodenal opacification) and gastroduodenal endoscopy were tools of diagnosis. Results: Our study involved 6 girls aged 4 to 12. Symptoms were epigastric pain associated with vomiting of recently ingested food in 3 cases and weight loss in one case. Physical examination found a hard epigastric mass in all cases. The trichobezoar was confined to the stomach in 4 cases. An extension into the jejunum was observed in 2 cases. Surgery was indicated in all patients. In two cases, the attempt of endoscopic extraction failed and patients were then operated on. All patients had gastrotomy to extract the whole bezoar even those with jejunal extension. Psychiatric follow-up was indicated in all cases. The six girls have evolved well and did not present any recurrence. Conclusion: open surgery still plays a crucial role in Trichobezoard management . After successful treatment, psychiatric consultation is imperative to prevent reccurrence and improve long term prognosis